Growth and development of male gymnasts, swimmers, soccer and tennis players: a longitudinal study - Baxter-Jones, A. D.; Helms, P.; Maffulli, N.; Baines-Preece, J. C.; Preece, M. (Annals of Human Biology, 1995)
Elite adult athletes are known to have physical and physiological characteristics specifically suited to their sport. However, it is not clear whether the observed adult differences arise because of training or whether the sport selects the individual with the appropriate characteristics. The purpose of this prospective study was to compare and contrast the physical development of young athletes (8-19 years), and in so doing provide a possible response to this question. Development of anthropometric characteristics and sexual maturation were assessed in a group of 232 male athletes for three consecutive years. Parental heights were used to predict target heights. The subjects were a randomly selected group of young British athletes, from four sports: soccer, gymnastics, swimming and tennis. Using a linked longitudinal cohort study design (age cohorts 8, 10, 12, 14 and 16 years) it was possible to estimate a consecutive 11-year development pattern, over the 3-year testing period. The adjusted mean (ANCOVA) height, accounting for age and pubertal status, of male swimmers (161.6 +/- 0.6 cm) was found to be significantly greater (p < 0.01) than gymnasts (150.7 +/- 0.8 cm) and soccer players (158.7 +/- 0.6 cm), and their adjusted mean body mass (51.3 +/- 0.6 kg) significantly greater (p < 0.01) than the other groups. When testicular volumes were compared, it was found that swimmers had significantly larger volumes than gymnasts and tennis players from 14 to 16 years of age (p < 0.05). Gymnasts' growth curve of testis size was characteristic of late maturers, the swimmers' curve was characteristic of early maturers. As all the young athletes started training prior to puberty the observed late sexual maturation of gymnasts and early maturation of swimmers suggests some form of sports-specific selection. Training did not appear to have affected these young athletes' growth and development; rather their continued success in sport appeared to be related to inherited traits.